Blockchain Technology and its Significance for Accounting - Khusinov Ibragim Ismailovich; Dilobar Dilshod kizi Mirsadikova (Periodica Journal, 2023)
The article discusses the possible implications of blockchain for accounting and what further developments are needed to create an integrated accounting system based on blockchain technology. The focus is on both accounting and auditing. The purpose of the article is to discuss the possible impact of blockchain on accounting practice from both a positive and negative point of view, as well as to determine what developments are needed to create an integrated accounting system based on blockchain technology.
Keywords: Accounting; Auditing; Blockchain; Cryptography